Chromatographic analysis and physicochemical evaluation of the essential oil of Bauhinia monandra Kurz flowers (Research, Society and Development, 2020)
The study of chromatographic techniques, classical and modern, describes the simplicity and, at the same time, the advances that this area has undergone in recent years in quality scientific research and also in learning in undergraduate and postgraduate courses around the world. This paper investigate a characterization by thin layer chromatography (TLC) and gas chromatography coupled with mass spectrometry (GC-MS), as a method developed by graduate students that involve a combination of a classic and modern technique, as well as results about the physicochemical properties of the essential oil of Bauhinia monandra flower. Essential oil was extracted by Clevenger, the TLC was performed in different eluents and developers, and thus the retention factors (Rfs), and the chemical profile by GC-MS were obtained. The essential oil of the flowers showed a yield of 0.06%, positive solubility in ethanol 70%, refractive index of 1.3621, optical rotation of +36.4αD and relative density of 0.941 g mL-1 at 20 °C. In the TLC analysis 18 Rfs were observed after the use of different developers, with the predominant class of oxygenates compounds. In the GC-MS analysis, 7 compounds were observed, being two majorities, characterized as panaxene with 20.51% and the α-guaiene with 33.39%. The essential oil of B. monandra flower showed a predominance of 70.22% of sesquiterpenic compounds. The allied techniques, classic and modern, demonstrated different ways of evaluating the essential oil through its chemical composition, both techniques showed high efficiency and precision, in addition was an appropriate project developed by postgraduate students.